1995
DOI: 10.1007/bf02348735
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for hepatic metastasis from colorectal cancer

Abstract: Hepatic micrometastases of the parenchyma adjacent to a macroscopic lesion were detected in 17 of 31 resected liver metastases. Fifty-nine micrometastatic lesions were detected in total; 26 lesions were situated in the portal vein (PV), 22 in the central vein (CV), 5 in the bile duct (BD), and 6 in the sinusoid (SS). A histological study confirmed the direct invasion of the macrometastatic cancer cells into the adjacent PV, CV, BD, and SS. According to the tumor doubling time, the mean diameter of the macromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Most recurrences after hepatectomy are likely to arise from occult tumors that are present at the time of resection [36]. Microscopic satellite lesions have been detected in vessels and bile ducts surrounding macroscopic lesions [14]. Most patients in stage III, whose macroscopic tumors have been completely resected, still harbor microscopic disease and, therefore, have much higher recurrence rates and a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recurrences after hepatectomy are likely to arise from occult tumors that are present at the time of resection [36]. Microscopic satellite lesions have been detected in vessels and bile ducts surrounding macroscopic lesions [14]. Most patients in stage III, whose macroscopic tumors have been completely resected, still harbor microscopic disease and, therefore, have much higher recurrence rates and a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…T-DT was calculated by the expression: log 2/3[(T 2 T 1 )/(log D 2 log D 1 )], where T 1 and T 2 are time and D 1 and D 2 are tumor diameter at any two time points in the clinical course prior to hepatectomy. CEA-DT was calculated by the expression, log 2[(T 2 T 1 )/(log C 2 log C 1 )], where T is time and C is CEA concentration, as previously reported [10][11][12][13][14]. We have shown that T-DT of the hepatic metastasis is highly correlated with the CEA-DT in patients with no extrahepatic metastases [14]; T-DT does not correlate with CEA-DT when extrahepatic metastases are present [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Takenami et al 3) and Shimada et al 23) also reported that the number of MiMs increased with increases in the size of the macrometastases.…”
Section: Discussionmentioning
confidence: 93%
“…Here, T1 and T2 represent two time points, and C1 and C2 are serum carcinoembryonic antigen (CEA) concentrations at the respective times before hepatectomy [15][16][17][18][19]. When CEA-DT was not measurable, we used tumor size DT (T-DT), which was calculated using the following equation:…”
Section: Patientsmentioning
confidence: 99%